Peningkatan Kualitas Pelayanan Dua Restoran Besar di Bandar Lampung melalui Pendekatan Dimensi Dineserve - Sipa Paujiah; Edwin Sutadipraja (Penerbit Goodwood, 2020)
Purpose: This research aimed to examine the quality of service at two large restaurants in Bandar Lampung using dineserv dimensions, data analysis using Important Performance Analysis (IPA) or presented using the Performance Analysis Index. Research Methodology: The study used primary data, and the data was obtained by distributing questionnaires to respondents. The sample in the study was 135 respondents, obtained using Hair et al (2010). The study was conducted for 3 months, from October to December 2021. Results: The result of this study is that Rumah Kayu restaurants should focus on providing comfortable chairs, educating employees with skills that can impress consumers. Limitation: On the other hand, Kinar restaurants should focus on providing better parking spaces, making facilities easy to use, and maintaining good service when the restaurant is crowded.